2011
DOI: 10.1007/s00787-011-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback in ADHD: a single-blind randomized controlled trial

Abstract: Neurofeedback treatment has been demonstrated to reduce inattention, impulsivity and hyperactivity in children with attention deficit/hyperactivity disorder (ADHD). However, previous studies did not adequately control confounding variables or did not employ a randomized reinforcer-controlled design. This study addresses those methodological shortcomings by comparing the effects of the following two matched biofeedback training variants on the primary symptoms of ADHD: EEG neurofeedback (NF) aiming at theta/bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
129
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(142 citation statements)
references
References 48 publications
4
129
0
4
Order By: Relevance
“…Several trials also evaluated the effect of NF on the EEG, and on learning EEG control during training. Frequency training NF compared to sham-NF has been found to effectively reduce Theta/Beta ratio during NF training and in a resting state baseline [18], and both SCP and frequency training can increase intentional control over brain electrical activity [38], although this may only hold for a subgroup of the ADHD children training with NF [45]. In a large randomized trial, the authors found SCP (when compared to CAST) to significantly decrease theta activity after training, and increase both participants capacity to modulate SCP, and Contingent Negative Variation (CNV) [54][55][56].…”
Section: Brain Electric Activity and Its Relation To Brain Functionmentioning
confidence: 96%
See 4 more Smart Citations
“…Several trials also evaluated the effect of NF on the EEG, and on learning EEG control during training. Frequency training NF compared to sham-NF has been found to effectively reduce Theta/Beta ratio during NF training and in a resting state baseline [18], and both SCP and frequency training can increase intentional control over brain electrical activity [38], although this may only hold for a subgroup of the ADHD children training with NF [45]. In a large randomized trial, the authors found SCP (when compared to CAST) to significantly decrease theta activity after training, and increase both participants capacity to modulate SCP, and Contingent Negative Variation (CNV) [54][55][56].…”
Section: Brain Electric Activity and Its Relation To Brain Functionmentioning
confidence: 96%
“…Almost unequivocally, uncontrolled within subjects' pre-to post-treatment analyses indicate positive results with medium-to-large effect sizes (ES) [16,18,21,35,[38][39][40][41][42][43][44][45][46][47].…”
Section: Brain Electric Activity and Its Relation To Brain Functionmentioning
confidence: 99%
See 3 more Smart Citations